Role of Social Business in Developing Countries: A Conceptual Framework - Salim Bhuyan, Mohammed; Raju, Valliappan; Poh Phung, Siew (International Journal of Psychosocial Rehabilitation, 2019)
Technological innovations profoundly impact society and business. In the post-industrial era, the most impactful of all is undoubtedly digital technology as we know it since the invention of computers, networks, the Web, mobile technologies and, increasingly social media and social technologies. Ever since we started connecting computers and created networks of computing power, data, information knowledge, people, devices and – increasingly – objects, the ways people communicate, buy, work and live evolved implementation and application of social business concept in various sectors of the economy, institutional framework required for social business, concluding remarks and recommendation for future.